Analisis Kesiapan Manajemen Terhadap Implementasi Perubahan Organisasi Pengelolaan SDM Single Grade di PT Pertamina (Persero) Marketing Operation Region V - Roy Stefanus Fanggidae; Dwi Ratmawati; Tri Siwi Agustina (Universitas Airlangga, 2015)
Current bussiness world move dynamically and require organization’s effectiveness in implementation of policy changes as a form of company's efforts towards becoming a World Class Company. Organizations mostly have always introduced large or minor changes which are adaptive. Therefore, any changes in organization must be planned and managed at best. The process of changes must be managed skillfully in order to effectively implemented align with the interests of the organization. PT Pertamina (Persero) had implemented Single Grade policy as the organization effort in the implementation of changes.These studies describe the process of change that have occured in PT Pertamina (Persero) Marketing Operation Region V with 17 (seventeen) key element of diagnosing changes by using the model of Readiness for change by Stewart namely sponsorship, leadership, motivation, direction, measurements, organizational context, processes or functions, competitor benchmarking, customer focus, rewards, organizational structure, communication, organizational hierarchy, prior experience with change, morale, innovation, and decision making. These studies used qualitative research method with explanatory type research (explanatory). These studies use a holistic case study, using interviews, observation and see the company's internal documents to obtain the necessary data.The results show that there is a real effort of PT Pertamina (Persero) Marketing Operation Region V in making changes. The process of changes shown in seventeen key elements of diagnosing changes resulted in increased employee performance. The company’s effort in implementing changes encouraged employees to improve their competence and self ability, and also to be fully responsible for the tasks given. The process of changes is still underway and requires continuous monitoring and evaluation, in order to understand the development of changes so it always evolving towards the better. Subsequent studies can be done with more evidence sources and different methods.